2018
DOI: 10.14744/nci.2018.79990
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Using Pediatric Emergency Rooms

Abstract: OBJECTIVE: The overload of pediatric emergency units around the world has become an increasing problem for patients and health care professionals alike. Researching the features of pediatric emergency services will provide the necessary information for creating an effective emergency medical system, increasing patient satisfaction, and reducing the treatment costs. In this study; we aimed to check the admissions in pediatric emergency rooms, evaluate the effectiveness of emergency service, and dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…33,34 In 2015, 30 million PED visits were reported in the United States, and children younger than 5 years accounted for more than 40% of them. 35 In Turkey, Temizkan et al 20 and Cag et al 36 reported that the admission rate of children under 5 years was 36% and 69%, respectively. Considering the distribution of admissions by age groups, Karakas et al 34 reported that the most common admission was in 1 month-6 years of age group (66%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…33,34 In 2015, 30 million PED visits were reported in the United States, and children younger than 5 years accounted for more than 40% of them. 35 In Turkey, Temizkan et al 20 and Cag et al 36 reported that the admission rate of children under 5 years was 36% and 69%, respectively. Considering the distribution of admissions by age groups, Karakas et al 34 reported that the most common admission was in 1 month-6 years of age group (66%).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was demonstrated that the frequency of upper respiratory tract infection increased in the winter months, and trauma cases increased in the spring and summer months. 20,25,36 In a systematic review, it was reported that the frequency of ED admission was highest in spring and lowest in winter. 25 However, the seasonal variations in childhood diseases, as opposed to adult diseases, might affect the admission diagnosis in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reasons why children are admitted to emergency care units are very similar around the world. Upper respiratory tract infections and other concerns within the respiratory system, [ 2 , 11 , 12 ] as well as injuries or trauma [ 1 , 13 , 14 ] have been identified as the most common reasons for pediatric emergency care in multiple descriptive studies. Other common reasons include gastrointestinal tract problems and general symptoms, such as fever [ 1 , 2 , 11 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Upper respiratory tract infections and other concerns within the respiratory system, [ 2 , 11 , 12 ] as well as injuries or trauma [ 1 , 13 , 14 ] have been identified as the most common reasons for pediatric emergency care in multiple descriptive studies. Other common reasons include gastrointestinal tract problems and general symptoms, such as fever [ 1 , 2 , 11 14 ]. Fever on its own was discovered to be behind 24% of pediatric emergency care visits in Switzerland during the winter months [ 15 ].…”
Section: Introductionmentioning
confidence: 99%